Local Culture-Based Arabic Language Learning in Islamic Schools within the Context of Global Education: Ethno-Edutainment as a Curriculum Innovation - Sovia Fahraini; M. Insan Hilmy; Nada Ibrahim Alribdi; Muzakki Abdurrahman; Muhammad Thohir (Nuris Journal of Education and Islamic Studies, 2026)
Arabic language learning in the global era demands linguistic mastery combined with cross-cultural competence. However, Arabic learning practices in Islamic schools (madrasah) in Indonesia are still textual and less contextual, so that students' interests and communicative skills are limited. This study aims to formulate a local culture-based Arabic language learning model through an ethno-edutainment approach as an adaptive curriculum innovation for the 21st century. The method used is library research with an analytical-critical approach, exploring the latest literature (2021–2025) related to Arabic language learning, local culture, edutainment, Islamic school, and global education. The analysis was carried out through content analysis and conceptual synthesis to design a holistic model framework. The results of the study indicate that: a) Arabic language learning in the challenges of global education, b) Local culture as a source of Arabic language learning, c) The concept of ethno-edutainment in a theoretical perspective, d) Design of a conceptual model for Arabic language learning based on ethno-edutainment, e) Opportunities and challenges of ethno-edutainment as a curriculum innovation in Islamic schools. The contribution of this research is theoretical by expanding the study of culture-based Arabic language learning, and practical as a guide for learning design, creative media development, and curriculum innovation that connects local identity with the demands of global education.